2020
DOI: 10.3390/antiox9100911
|View full text |Cite
|
Sign up to set email alerts
|

Dendropanax morbifera Leaf Extracts Improved Alcohol Liver Injury in Association with Changes in the Gut Microbiota of Rats

Abstract: This study evaluated the protective effects of Dendropanax morbifera leaf (DML) extracts in the liver due to excessive ethanol consumption. Our results showed that the ethanol extract had better antioxidant activity than the water extract, likely due to the higher levels of total flavonoid and phenolic compounds in the former. We found that the main phenolic acid was chlorogenic acid and the major flavonoid was rutin. Results from the animal model experiment showed concentration-dependent liver protection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Some alternative and complimentary remedies, such as traditional herbal medicines in China [ 260 , 261 , 262 ], Korea [ 263 ], and India [ 264 , 265 ], have recently proved effective in both combatting inflammation and in altering the gut microbial composition in models of ALD or models of intestinal disease. For example, co-administration of ethanol with the fungi Wolfporia cocos (or, more specifically, the water-insoluble polysaccharides from their fruiting bodies) decreased the hepatic triglyceride levels and MCP-1 levels, indicating decreased steatosis and inflammation of the liver [ 261 ].…”
Section: Translational Approaches and Therapeutics Against Alcoholmentioning
confidence: 99%
See 2 more Smart Citations
“…Some alternative and complimentary remedies, such as traditional herbal medicines in China [ 260 , 261 , 262 ], Korea [ 263 ], and India [ 264 , 265 ], have recently proved effective in both combatting inflammation and in altering the gut microbial composition in models of ALD or models of intestinal disease. For example, co-administration of ethanol with the fungi Wolfporia cocos (or, more specifically, the water-insoluble polysaccharides from their fruiting bodies) decreased the hepatic triglyceride levels and MCP-1 levels, indicating decreased steatosis and inflammation of the liver [ 261 ].…”
Section: Translational Approaches and Therapeutics Against Alcoholmentioning
confidence: 99%
“…Interestingly, these polysaccharides increased Firmicutes abundance and decreased the abundance of the Gram-negative, LPS-producing Proteobacteria phylum following chronic alcohol exposure [ 261 ]. Additionally, leaf extract from the plant Dendropanax morbifera leaf extract also altered microbial composition in rats acutely exposed to alcohol, whereby, for example, members of the Bacteroides operational taxonomic unit (OTU) increased upon co-administration of leaf extract with ethanol, compared to the ethanol group [ 263 ]. The Dendropanax morbifera leaf extract co-administered with ethanol contained several phytochemicals (e.g., rutin, caffeic acid, etc.)…”
Section: Translational Approaches and Therapeutics Against Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidants have been used in food, cosmetics, and pharmaceutics; among them, phenolic acids are major plant compounds that possess antioxidant capacity [9]. Caffeic acid (CA) and chlorogenic acid are representative phenolic acids in D. morbifera [10]. Previous studies have revealed the antioxidant capacity [11][12][13], antiviral [14], anti-inflammation [15], anti-cancer [16,17], and neuroprotective [12,18] effects of CA.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid exhibits antioxidant and DNA-protective activities [19], along with anti-inflammation [20], anticancer [21], antibacterial, and anti-biofilm activities [22]. Therefore, the antioxidant capacity of phenolic acids from D. morbifera has been extensively reported [10,23].…”
Section: Introductionmentioning
confidence: 99%